Social capital and network governance in local anti-poverty policy - Kaliky, Pahrul Idham; Titaley, Elsina (Faculty of Communications Science, Dr. Soetomo University, 2026)
This study examined the effectiveness of public sector organisational communication in poverty alleviation efforts in West Seram Regency (SBB) through the lenses of Social Capital Theory, Integrated Marketing Communication (IMC), and network governance. Poverty is conceptualised as a multidimensional issue requiring cross-sectoral coordination and multi-actor collaboration. This research employed a qualitative descriptive approach centred on document analysis of the 2025–2029 Regional Poverty Alleviation Plan (RPKD) and relevant scholarly sources. The findings indicate that communication effectiveness is shaped by levels of trust and inter-actor networks (social capital), the consistency and integration of cross-agency messaging (IMC), and the capacity for horizontal and vertical coordination within a network governance framework. Sectoral and administrative communication patterns tend to produce fragmented programmes and policy overlap. Therefore, strengthening collaborative and participatory communication mechanisms is essential to achieving more integrated, effective, and sustainable poverty governance in West Seram Regency.